Development of a dextrin-based hydrogel for bone regeneration - Silva, Dina M. (2014)
[Excerpt] Bone tissue engineering is a very challenging and promising field, which handles with the limitations of bone regenerative capacity and the failure of current orthopedic implants [1]. This work describes the preparation and characterization of an injectable dextrin-based hydrogel (oDex) able to incorporate nanoparticles, cells, biomolecules or Bonelike~ granules [2]. (...)